Molecular mechanism of endophytic bacteria DX120E regulating polyamine metabolism and promoting plant growth in sugarcane - Qin, Ying; Khan, Qaisar; Yan, Jia-Wei; Wang, Yu-Yi; Pan, Yang-Fei; Huang, Ying; Wei, Jiang-Lu; Guo, Dao-Jun; Li, Yang-Rui; Dong, Deng-Feng; Xing, Yong-Xiu (Frontiers in Plant Science, 2024)
ABSTRACT Sugarcane endophytic nitrogen-fixing bacterium Klebsiella variícola DX120E displayed broad impact on growth, but the exact biological mechanism, especially polyamines (PAs) role, is still meager. To reveal this relationship, the content of polyamine oxidase (PAO), PAs, reactive oxygen species (ROS)-scavenging antioxidative enzymes, phytohormones, 1-aminocyclopropane-1-carboxylic synthase (ACS), chlorophyll content, and biomass were determined in sugarcane incubated with the DX120E strain. In addition, expression levels of the genes associated with polyamine metabolism were measured by transcriptomic analysis. Genomic analysis of Klebsiella variícola DX120E revealed that 39 genes were involved in polyamine metabolism, transport, and the strain secrete PAs in vitro. Following a 7-day inoc-ulation period, DX120E stimulated an increase in the polyamine oxidase (PAO) enzyme in sugarcane leaves, however, the overall PAs content was reduced. At 15 days, the levels of PAs, ROS-scavenging antioxidative enzymes, and phytohormones showed an upward trend, especially spermidine (Spd), putrescine (Put), catalase (CAT), auxin (IAA), gibberellin (GA), and ACS showed a significant up-regulation. The GO and KEGG enrichment analysis found a total of 73 differentially expressed genes, involving in the cell wall (9), stimulus response (13), peroxidase activity (33), hormone (14) and polyamine metabolism (4). This study demonstrated that endophytic nitrogen-fixing bacteria stimulated polyamine metabolism and phytohormones production in sugarcane plant tissues, resulting in enhanced growth. Dual RNA-seq analyses provided insight into the early-stage interaction between sugarcane seedlings and endophytic bacteria at the transcriptional level. It showed how diverse metabolic processes selectively use distinct molecules to complete the cell functions under present circumstances.